Isostructural metal organic frameworks based on 1, 4-naphthalene dicarboxylate as anodes for lithium ion battery. (24th August 2017) - Gou, Lei; Liu, Peng-Gang; Lei, Hao-Yu; Chen, Guang-Qi; Li, Zhao-Yang; Fan, Xiao-Yong; Li, Dong-Lin; Song, Li-Fang
Abstract: Metal organic frameworks (MOFs) emerged as a kind of promising electrode material have attracted considerable attentions in recent years. In this work, two 1, 4-naphthalene dicarboxylate based MOFs, namely, Mn2 (NDC)2 (DMF)2 and Cd2 (NDC)2 (DMF)2 are synthesised by a solvothermal method and characterised by IR, XRD, TGA, SEM. Their electrochemical performances as anode materials for lithium ion battery are investigated for the first time. The result indicates both compounds showing single crystal feature with a bar shape can exhibit electrochemical reactivity. However, Mn2 (NDC)2 (DMF)2 has higher specific capacity in compared with Cd2 (NDC)2 (DMF)2 . The reversible specific capacities of Mn2 (NDC)2 (DMF)2 at current density of 200, 500, 1000 mAg –1 after 300 cycles maintain at 765.4, 524.4 and 309.3 mAhg –1, respectively, while the values are 401.8, 296.1 and 266.5 mAhg –1 for Cd2 (NDC)2 (DMF)2 .